2019
DOI: 10.2139/ssrn.3318327
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Functional Fee Market for Cryptocurrencies

Abstract: Blockchain-based cryptocurrencies prioritize transactions based on their fees, creating a unique kind of fee market. Empirically, this market has failed to yield stable equilibria with predictable prices for desired levels of service. We argue that this is due to the absence of a dominant strategy equilibrium in the current fee mechanism. We propose an alternative fee setting mechanism that is inspired by generalized second price auctions. The design of such a mechanism is challenging because miners can use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 39 publications
(16 reference statements)
3
29
0
Order By: Relevance
“…Only a few recent work touched upon the issue of how miners select and order transactions, and how this is interlaced with how the fees are set. Lavi et al [40] and Basu et al [6] highlighted the inefficiencies in the existing transaction fee-setting mechanisms and proposed alternatives. They showed that miners might not be trustworthy, but without providing empirical evidence.…”
Section: Related Workmentioning
confidence: 99%
“…Only a few recent work touched upon the issue of how miners select and order transactions, and how this is interlaced with how the fees are set. Lavi et al [40] and Basu et al [6] highlighted the inefficiencies in the existing transaction fee-setting mechanisms and proposed alternatives. They showed that miners might not be trustworthy, but without providing empirical evidence.…”
Section: Related Workmentioning
confidence: 99%
“…Step 3: In each transaction, we treat all the addresses on the input side of a transaction as being controlled by the same person. 6 In the first step, we filter out all the users who only use addresses once for any transaction and may care more about transaction privacy than returns, along with the users who do not trade frequently. In this study, we use monthly returns, half-monthly returns, and weekly returns to measure investors' performance on a short-term horizon.…”
Section: Data Parsingmentioning
confidence: 99%
“…Dimitri [18] models "the transaction fee as a Nash equilibrium outcome of an auction game with complete information," and the conclusion is that the optimal block size for miners depends on the distribution of users' willingness to pay. Basu et al [6] argue that the transaction fee mechanism in the bitcoin system acts as a generalized first-price auction on multiple and identical items. Noda et al [41] point out a potential vulnerability in the bitcoin payment system: the difficulty adjustment algorithm in the bitcoin network may fail to adjust the block arrival rate timely when a large group of miners suddenly leave the network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid price fluctuation, the authors in [34] proposed a new method to compute fees based on generalized second price auctions that will reduce the gain obtained by manipulating the system, even if the number of users increases. A game theory approach to study fees can be found in [35] in which the authors show that the current state of the system incentivizes the formations of large miner coalitions.…”
Section: Related Workmentioning
confidence: 99%